The Authority of Ulama towards Politics: The Role of Teungku, Tuan Guru and Kiai in Nation Below the Wind - M. Alkaf; Muhammad Said; Saiful Hakam (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This article discussed the relationship between ulama and politics in three types of elite Islamic leadership in Indonesia: Teungku in Aceh, Tuan guru in Lombok, Nusa Tenggara Barat, and Kiai in Java. The research was organized based on the central questions; what was the political role of Teungku, Tuan guru, and Kiai, and what was their authority in the dynamics of local and national politics? This research used qualitative methods with an ethnographic approach. Data was collected through direct observation, interviews, review of written sources, and documentation data. This article found that Teungku, Tuan guru, and Kiai, in addition to being religious elites, also played the role of political elites. With the capital of religious authority at their disposal, they were confident to engage in practical politics. Teungku in Aceh was actively involved in redefining the narrative of the Acehnese nation by promoting the formalization of Islamic Sharia through a policy of special autonomy. With this policy, Teungku's position became more substantial and strategic politically and religiously. While in Lombok, Tuan guru became a local strongman who seized legislative and executive power in Nusa Tenggara Barat. They succeeded in seizing local power from the Sasak aristocratic circles. Meanwhile, Kiai in Java appeared to color Indonesia's discourse and political system from the beginning. Nevertheless, they managed to become part of the power in national leadership history. The relationship of the three religious elites to politics was ultimately in line with the strengthening of authority, religious traditions, and religious institutions.